Multicultural Education in Inter-language English Textbooks for Senior High School Students in Maroangin - Mustakim, Mustakim; Lateh, Nurisan (Majesty Journal, 2020)
This study aims: (1) to describe and explain the multicultural education content in Interlanguage English textbooks of senior high school level, and (2) to describe and explain the quality of the multicultural education content in Interlanguage English textbooks of senior high school level. The form of this research was descriptive qualitative. The data sources in this study were Interlanguage English textbooks of senior high school in Maroangin and informants, namely the authors of the books analyzed. Data collection techniques using content analysis techniques, questionnaires, and in-depth interviews. Test the validity of the data with the theory and source triangulation techniques, while data analysis used interactive analysis techniques. Based on the results of the study it can be concluded that: (1) the contents of multicultural education in the analyzed Interlanguage English textbooks do not fully contain the dimensions of multicultural education. This was evident from the five dimensions that should have existed only three dimensions were raised, namely the dimensions of material integration, the dimension of reducing prejudice, as well as the dimensions of strengthening school culture and social structure. Whereas the other two dimensions, namely the dimension of knowledge construction and the dimension of adjustment of learning methods were not found in the textbook; (2) the quality of multicultural education content in the lessons is still very inadequate. This is because not all multicultural dimensions are integrated in the textbook.